2017
DOI: 10.1021/acs.molpharmaceut.7b00308
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab Prevents Methotrexate-Induced Cytotoxicity in Vitro through Epidermal Growth Factor Dependent Regulation of Renal Drug Transporters

Abstract: The combination of methotrexate with epidermal growth factor receptor (EGFR) recombinant antibody, cetuximab, is currently being investigated in treatment of head and neck carcinoma. As methotrexate is cleared by renal excretion, we studied the effect of cetuximab on renal methotrexate handling. We used human conditionally immortalized proximal tubule epithelial cells overexpressing either organic anion transporter 1 or 3 (ciPTEC-OAT1/ciPTEC-OAT3) to examine OAT1 and OAT3, and the efflux pumps breast cancer re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 57 publications
1
27
0
Order By: Relevance
“…Interestingly, there was an increase in hepatic Abcb1a/b expression levels (Fig. 7C), which is in line with another study that assessed changes in transporter expression levels in human conditionally immortalized proximal tubule epithelial cells after treatment with the EGFR recombinant antibody cetuximab; significant decreases occurred in ABCG2 mRNA and increases were seen in ABCB1 mRNA (Caetano-Pinto et al, 2017). Our data thus support the premise that hepatobiliary excretion of [ 11 C]erlotinib is, to a larger extent, dependent on Abcg2 than on Abcb1a/b, as k bile was decreased in EGFR Δhep mice despite an apparent upregulation of canalicular Abcb1a/b.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, there was an increase in hepatic Abcb1a/b expression levels (Fig. 7C), which is in line with another study that assessed changes in transporter expression levels in human conditionally immortalized proximal tubule epithelial cells after treatment with the EGFR recombinant antibody cetuximab; significant decreases occurred in ABCG2 mRNA and increases were seen in ABCB1 mRNA (Caetano-Pinto et al, 2017). Our data thus support the premise that hepatobiliary excretion of [ 11 C]erlotinib is, to a larger extent, dependent on Abcg2 than on Abcb1a/b, as k bile was decreased in EGFR Δhep mice despite an apparent upregulation of canalicular Abcb1a/b.…”
Section: Discussionsupporting
confidence: 89%
“…21 Studies in mice and humans have suggested that ABCG2, coding for the breast cancer resistance protein (BCRP) transporter has a major role in transporting MTX out of the liver and kidney. 39,40 BCRP is a multidrug transporter expressed in many tissues, 41 including the human kidney proximal tubule apical membrane. 42 In our cohort, GG genotype carriers for rs13120400 appear to have a moderate decrease on MTX exposure compared to AA or GA carriers under a recessive genetic model.…”
Section: Discussionmentioning
confidence: 99%
“…Human-derived immortalized renal cell models such as human embryonic kidney 293 (HEK 293) and human kidney 2 (HK 2) cells have shown to be a valuable tool in screenings in drug development, but have low or no endogenous expression of relevant drug transporters (48,49). To overcome these limitations, we have developed ciPTEC-OAT1 with proven suitability for nephrotoxicity and drug-transporter interactions studies (10)(11)(12)(13)(14). The broad range of drug transporter expression in ciPTEC-OAT1 provides a strong basis for highly predictive renal drug interaction studies.…”
Section: Discussionmentioning
confidence: 99%
“…Further transduction resulted in stable expression and functionality of OAT1 or OAT3 (10). Multiple studies have shown the potential of ciPTEC for studying drug transport and drug-induced toxicity cultured under conventional static conditions, often referred to as two-dimensional (2D) cell culture (10)(11)(12)(13). In addition, transepithelial barrier function, polarization, and transport of cations and anions have been demonstrated in ciPTEC cultured in a threedimensional (3D) model using a tailor-made hollow fiber membrane system exposed to flow (13,14).…”
Section: Introductionmentioning
confidence: 99%